2012
DOI: 10.1108/ijotb-15-03-2012-b003
|View full text |Cite
|
Sign up to set email alerts
|

Something old and something new: Using the technology acceptance model to evaluate nonprofit certification

Abstract: Several nonprofit associations have implemented assessment and certification programs intending to produce institutional improvement for member organizations. Using the Technology Acceptance Model (TAM) as a foundation, this study develops and tests an extension of TAM with organizations that chose to participate in one such program, (the Louisiana Standards for Excellence organizational assessment), and with those that did not. The results of this quantitative study largely validate TAM and indicate that dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Hume ( 2015 ) combined the concept of service quality and value with the TAM to study customer technology at museums. Slatten ( 2012 ) used the TAM to explain participation in nonprofit certification programs. Zheng ( 2020 ) and Weberling and Waters ( 2012 ) integrated the TAM into their research model on mobile fundraising technology.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Hume ( 2015 ) combined the concept of service quality and value with the TAM to study customer technology at museums. Slatten ( 2012 ) used the TAM to explain participation in nonprofit certification programs. Zheng ( 2020 ) and Weberling and Waters ( 2012 ) integrated the TAM into their research model on mobile fundraising technology.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…This study was supported by previous study (Hubert, et al, 2019;Marakarkandy, et al, 2017;Singh, et al, 2006) that used theory of acceptance model in their research. In addition, perceived ease of use (Rauniar, et al, 2014;Teo et al, 2011;David, 1989) and perceived usefulness (Ben Mansour, 2016;Slatten, 2012;Sheikhshoaei, and Oloumi, 2011) found to statistically significant. Study that used religiosity as one of the variable also found to be statistically significant (Amin, et al, 2014;Mokhlis, 2009;Abdullah and Abd-Majid, 2003).…”
Section: Structural Model For Hypothesis Testing Using Unstandardizedmentioning
confidence: 93%
“…According to Lee [4] TAM is the most determining theory applied to figure out an individual's acceptance towards the Information System (IS) whereas TAM was adapted from the Theory of Reasoned Action (TRA). Figure 5 shows the Technology Acceptance Model according to Davis in Slatten [5]. Figure 2 represents two beliefs; the Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) which are considered as the main connection of technology acceptance behaviour.…”
Section: A State Of the Art Of The Research 1) Technology Acceptancementioning
confidence: 99%